SARS‐CoV‐2 memory B and T cell profiles in mild COVID‐19 convalescent patients. (February 2022) - Gurevich, Michael; Zilkha-Falb, Rina; Sonis, Polina; Magalashvili, David; Menascu, Shay; Flechter, Shlomo; Dolev, Mark; Mandel, Mathilda; Achiron, Anat
Highlights: COVID-19 convalescents displayed an adaptive immune response for up to 7 months. The T cell response is characterized by IFN-γ-, IL2-, and IFN-γ+IL2-secreting memory T cells. Waning anti-SARS-CoV-2 IgG is associated with robust memory B cell and memory T cell responses. The SNMO peptide pools elicited the strongest memory T cell response. Abstract: Objectives: Antiviral adaptive immunity involves memory B cells (MBC) and memory T cells (MTC). The dynamics of MBC and MTC in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) convalescents warrant further investigation. Methods: In this cross-sectional and longitudinal study, blood-derived MBC and MTC responses were evaluated in 68 anti-spike IgG-positive mild coronavirus disease 2019 (COVID-19) convalescents at visit 1, between 1 and 7 months (median 4.1 months) after disease onset. SARS-CoV-2 anti-spike IgG was determined by ELISA, MBC by SARS-CoV-2-specific receptor binding domain (RBD) ELISpot, and interferon gamma (IFN-γ)-, interleukin 2 (IL2)-, and IFN-γ+IL2-secreting MTC by IFN-γ and IL2 SARS-CoV-2 FluoroSpot. For 24 patients sampled at the first visit, the IgG, MBC, and MTC analyses were also performed 3 months later at the second visit. Results: Seventy-two percent of convalescents were both MBC- and MTC-positive, 18% were MBC-positive and MTC-negative, and 10% were MTC-positive and MBC-negative. The peak MBC response level was detected at 3 months after COVID-19 onset and persisted up to 7 months post infection. Significant MTC levels were detected 1 month after onset in response to S1, S2_N, and SNMO peptide pools. The frequency and magnitude of the MTC response to SNMO was higher than those to S1 and S2_N. Longitudinal analysis demonstrated that even when specific humoral immunity declined, the cellular immunity persisted. Conclusions: The study findings demonstrate the durability of adaptive cellular immunity at least for 7 months after SARS-CoV-2 infection, suggesting long-lasting protection.